Performance evaluation of water delivery system of Mahanadi delta irrigation project, Odisha - PAUL, J. C.; PANIGRAHI, B. (Journal of Soil and Water Conservation, 2018)
This paper deals with evaluation of performance of water delivery system of Phiriphira distributary of Puri main canal in Mahanadi Delta irrigation command of Odisha. The performance parameters like adequacy, efficiency, equity and dependability were estimated and the results are presented and discussed. The study is carried out with daily discharge and crop water requirement data. The average values of estimated efficiency parameter of 0.76 to 0.81 indicate that water delivery system in the command is fair. Similarly, the average estimated values of equity were obtained between 0.14 and 0.24 that indicates fairness in canal water delivery system in the canal section. The average values of dependability were 0.31, 0.17 and 0.14 for head, middle and tail reaches, respectively which indicates that the dependability on the system was poor in head reach, but fair in middle and tail reaches. On an average, there is fair distribution of canal water delivery system in Mahanadi Delta irrigation command of Odisha.